Rules and regulations - West African clearing house (West African clearing house, 1986)
This hand booklet is a compilation of basic rules and regulations of the West African clearing house on banks, banking and related financial activities.
asm; 16/04/19
Loans
Keywords: Banks and banking; Deposit insurance; West African countries